Thamnophilidae (antbird) molt strategies in a central Amazonian rainforest - Johnson, Erik I.; Wolfe, Jared D. (Wilson Journal of Ornithology, 2014)
Avian molt, or the regularly scheduled replacement of feathers, is an important life history event, particularly in central Amazonian rainforest birds for which a relatively high proportion of the annual cycle can be dedicated to this process. Here, we detail molt strategies of 18 antbird species (Thamnophilidae) based on 2,362 individuals captured from lowland tropical rainforest at the Biological Dynamics of Forest Fragmentation Project near Manaus, Brazil. All species exhibited a molt strategy consistent with the Complex Basic Strategy, in which birds undergo an inserted preformative molt within the first cycle, but apparently lack prealternate molts. The preformative molt and resulting formative plumage aspect of the 18 antbird species can be grouped by three distinct patterns: 1) a complete molt resulting in an adult-like formative plumage without molt limits; 2) a partial molt involving body feathers, lesser coverts, at least some or all median and greater coverts, and sometimes tertials or rectrices, resulting in an adult-like formative plumage with molt limits; and 3) a partial molt as in '2' but resulting in an adult female-like formative plumage in both sexes with plumage maturation delayed in males until the second prebasic molt. In addition, we show that one species, Percnostola rufifrons, exhibited an extra inserted molt (a partial auxiliary preformative molt) in the first cycle before initiating a complete preformative molt making this, to our knowledge, the first description of an auxiliary preformative molt for a suboscine. The extent of the preformative molt or delayed plumage maturation was not predicted by ecological guild, raising questions about how phylogenetic relatedness and ecological adaptation drive variation in molt patterns across antbirds. © 2014 by the Wilson Ornithological Society.
Keywords: Adaptation; Adult; Annual Cycle; Insectivory; Maturation; Molt; New Record; Passerine; Plumage; Rainforest; Relatedness; Tropical Forest; Understory; Amazonas; Manaus; Aves; Percnostola Rufifrons; Thamnophilidae